Transport Structure of the South Atlantic Ocean Derived From a High-Resolution Numerical Model and Observations - Xu, Xiaobiao; Chassignet, Eric P.; Dong, Shenfu; Baringer, Molly O. (Frontiers in Marine Science, 2022)
The South Atlantic Ocean plays an important role in the Atlantic meridional overturning circulation (AMOC), connecting it to the Indian and Pacific Oceans as part of the global overturning circulation system. Yet, there are still open questions regarding the relative importance of the warm water versus cold water sources in the upper limb of the AMOC and on the detailed circulation pathways of the North Atlantic Deep Water (NADW) in the lower limb. These questions are addressed using model outputs from a 60-year, eddying global ocean-sea ice simulation that are validated against observations. We find that the Pacific Antarctic Intermediate Water (AAIW) plays a role in setting the temperature and salinity properties of the water in the subtropical South Atlantic, but that the upper limb of the AMOC originates primarily from the warm Indian water through the Agulhas leakage (9.8 Sv of surface water + 3.5 of AAIW) and that only a relatively small contribution of 1.5 Sv colder, fresher AAIW originates from the Pacific Ocean. In the lower limb, the NADW flows southward as a deep western boundary current all the way to 45°S and then turns eastward to flow across the Mid-Atlantic Ridge near 42°S before leaving the Atlantic Ocean, although there is clockwise recirculation in the Brazil, Angola, and Cape Basins.